Fused deposition modelling interfacial and interlayer bonding in PLA post-processed parts. Issue 3 (9th December 2019) - Valerga Puerta, Ana P.; Fernandez-Vidal, S.R.; Batista, Moises; Girot, F.
Abstract : Purpose: This paper aims to study the interfacial and interlayer bonding of Polylactic acid parts manufactured by fused deposition modelling. Different layer thicknesses are analysed in the manufacture of these pieces and the lack of material associated with this parameter is verified. The influence of the immersion of these parts in different solvents is also studied, as they are increasingly used in the improvement of the surface finish. Tomography results are also obtained in which the increase in density of the parts subjected to these treatments is demonstrated. Design/methodology/approach: The material used in this study is a 1.75-mm diameter polylactic acid (PLA) filament from fused filament fusion world. Monolayer and multilayer samples have been manufactured. The manufactured parts were subjected to solvent immersion for a period of 60 s. The solvents used are chloroform (CHCl3), dichloromethane (CH2Cl2), tetrahydrofuran (C4H8O) and ethyl acetate (C4H8O2). The pieces were then dried for 48 h. The interior of the samples was evaluated by two techniques: microscopy and tomography. Findings: With this study, it has been observed that the thickness of the layer affects the porosity interfacial to a greater extent than in the interlayer, causing the increase in porosity as this thickness is increased.The impact of different chemical treatments (immersions in different solvents) on the internal quality of the parts has been evaluated. All the solvents analysed soften the surface as they cause the softening of the material and its possible redistribution. In the interior, however, they affect in a lighter way. The retention of solvents in the porosity of the pieces is also checked, especially pronounced in the areas close to the surface. Finally, changes are observed in the density of the pieces, related to the partial crystallization of the samples. Originality/value: All that has been studied shows that the application of chemical post-processes not only affects the surface texture of the parts, or the less studied mechanical properties, but also affects the interfacial union of the parts in a very different way. This is the first study carried out on this aspect with polylactic acid (PLA) and post-processing methods.